Hubungan Efikasi Diri Dan Dukungan Sosial Keluarga Terhadap Pengambilan Keputusan Karir Remaja Etnis Minang - Mulia Yunanda, Gita, Siti Nurina Hakim, S.Psi, M.Si, Psi (2018)
Career decision making was an important step for adolescent. Career decision making is one of them realized through the selection of majors. Important factors affecting career decision making are self efficacy and family social support. This study aims to examine the relationship between self efficacy and family social support to career decision making in minang adolescent. Participants in this study were students of level XII SMA N 2 Sijunjung which is 135 students. Sampling was done by cluster random sampling technique. The method used in this research is quantitative with career decision scale, self-efficacy scale, and family social support scale. Data analysis technique used in this research is multiple linear regression analysis. Based on the results of data analysis, the correlation (r) of 0.598 and significance (p) is 0.000 (p ≤ 0,01), meaning that there is a very significant relationship between self-efficacy and social support of family to career decision-making in Minang adolescent. Data analysis also showed that there is a significant positive correlation between self-efficacy and career decision making in Minang adolescent with rx1y correlation of 0,592 with significance (p) 0.000 (p ≤ 0,01). Moreover, there is a very significant positive relationship between the social support of the family and career decision making in Minang adolescent with rx2y correlation of 0.392 with significance (p) of 0.000 (p ≤ 0.01). Effective contribution (SE) of self-efficacy and social support of family to career decision making in Minang adolescent equal to 35,7% and there are still 64,3% other factors that influence career decision making.